Exploring Disparities in Youth Physical Activity Environments by Income and Non-Hispanic White Population Across the United States. Issue 2 (March 2022) - Wende, Marilyn E.; Stowe, Ellen W.; Hallum, Shirelle H.; Eberth, Jan M.; Liese, Angela D.; Kaczynski, Andrew T.
Abstract : This study investigated relationships between youth physical activity (PA) environments and income and non-Hispanic White population across the United States, stratified by US Census region and urban-rural designation. For all counties (n = 3142), publicly accessible data were used for sociodemographic indicators (ie, median household income and percent non-Hispanic White population) and a composite PA environment index (including exercise opportunities, violent crime incidence, walkability, and access to public schools). One-way analysis of variance was used to examine differences in PA environment index values according to income and non-Hispanic White population tertiles. There were significant differences in PA environments according to tertiles of income ( F = 493.5, P < .001) and non-Hispanic White population ( F = 58.6, P < .001), including variations by region and urban-rural designation. Public health practice and policy initiatives, such as joint use agreements, Safe Routes to School programs, and targeted funding allocations, should be used to address more pronounced income-based disparities in Southern and metropolitan counties and race-based disparities in rural and micropolitan counties.